Free Nutritious Meals (MBG) and the Enhancement of Human Development in the Perspective of Islamic Economics - Khoirudin, Ahmad; Kaharudin, M. Robby; Purwandari, Elce (Journal of Economics and Social Sciences (JESS), 2025)
The Free Nutritious Meal (Makan Bergizi Gratis/MBG) program is one of the strategic policies of the Indonesian government aimed at improving the quality of human resources through health and education interventions. This study examines MBG from the perspective of Islamic economics, focusing on its relevance to the principles of justice, welfare distribution, and social equity. The research employs a qualitative descriptive approach by analyzing government policy documents, statistical data, and relevant literature, supported by the Islamic economic framework. The findings reveal that MBG not only provides direct benefits in improving students’ nutritional intake but also contributes significantly to the Human Development Index (HDI) through increased school attendance, learning productivity, and reduced inequality in access to basic needs. In the perspective of Islamic economics, MBG reflects the values of maslahah (public benefit) and ta’awun (mutual assistance), thereby aligning with the objectives of maqasid al-shariah in preserving life (hifz al-nafs) and intellect (hifz al-‘aql). The novelty of this research lies in integrating the analysis of a national nutrition-based welfare program with the conceptual framework of Islamic economics, offering an alternative lens for evaluating social policies. This study emphasizes that MBG has the potential to serve not only as a public welfare policy but also as a realization of Islamic economic principles in fostering inclusive and sustainable human development.